Characterizing ionospheric perturbations with refined gradient ionosphere indices - Norbert Jakowski; M. Mainul Hoque; Juan Andrés Cahuasquí; Grzegorz Nykiel (GPS Solutions, 2026)
Precision and safety-critical Global Navigation Satellite System (GNSS) applications require high-fidelity monitoring of space weather conditions, particularly ionospheric disturbances. These systems are highly sensitive to sharp spatial gradients and rapid Total Electron Content (TEC) variations. To support both operational and scientific needs, this study proposes and evaluates two variants of the Gradient Ionosphere indeX (GIX): GIXM and GIXV. Derived from absolute TEC measurements at pairs of ionospheric piercing points (IPPs), the GIX quantifies gradients by dividing the TEC difference by the distance between IPPs. The GIXM method calculates the scalar average of these gradients, while GIXV computes the resultant gradient vector over regional scales (typically ≥ 500 × 500 km 2 ) to capture both magnitude and direction. Comparative analysis reveals a strong correlation between GIXM and the operational geodetic I95 index, confirming GIXM’s utility for disturbance scaling and reliability assessment. Accurate estimation of the GIXV vector requires sufficient spatial coverage, typically involving 35–45 IPPs. Furthermore, analyzing GIX dynamics within the Magnetosphere-Ionosphere-Thermosphere (MIT) framework demonstrates potential for predictive modeling. By tracking the equatorward propagation of high-latitude gradient structures, this framework enables the forecasting of GIXM I95 levels, offering a robust tool for mitigating GNSS risks.

The COSPAR international space weather action teams (ISWAT) initiative: a driving force for the COSPAR space weather roadmap - Maria M. Kuznetsova; Mario M. Bisi; Hermann J. Opgenoorth; Martin A. Reiss; M. Leila Mays; Lucilla Alfonsi; C. Nick Arge; David Barnes; Anna Belehaki; Thomas E. Berger; Amanda Brecht; Sean Bruinsma; et al. (Advances in Space Research, 2026)

Association between Arsenic Exposure and CCL5: its Implications in Asthma and Skin Lesions - Osman Goni; Nesar Uddin; Rajoana Karim Rimi; Kamrun Nahar Rossi; Faysal Abedin; Sharmin Akter Beauty; Sharon Jahan Sarder; Junayed Sadi; Mainul Islam; Victor Mondal; K M Ahsanul Kabir; Abu Eabrahim Siddique; et al. (Exposure and Health, 2026)

Relationship of fractalkine with arsenic exposure and the risk of cardiovascular diseases - Nesar Uddin; Rajoana Karim Rimi; Osman Goni; Nayan Chandra Mohanto; Kamrun Nahar Rossi; Faysal Abedin; Sharmin Akter Beauty; Biplob Ahmed; Sobuj Mia; Sharon Jahan Sarder; Sajib Hossain; Mainul Islam; et al. (Environmental Toxicology and Pharmacology, 2025)

Seasonal morphology and solar activity dependence analysis of mid-latitude post-midnight enhancement using Global Ionospheric Map - Eman M. El-Desoky; Mohammed Mainul Hoque; M. Youssef; Ayman Mahrous (Advances in Space Research, 2024)

Ionosphere variability II: Advances in theory and modeling - Ioanna Tsagouri; David R. Themens; Anna Belehaki; Ja-Soon Shim; Mainul M. Hoque; Grzegorz Nykiel; Claudia Borries; Anna Morozova; Teresa Barata; Wojciech J. Miloch (Advances in Space Research, 2023)

Ionosphere variability I: Advances in observational, monitoring and detection capabilities - Ioanna Tsagouri; Anna Belehaki; David R. Themens; Norbert Jakowski; Tim Fuller-Rowell; Mainul M. Hoque; Grzegorz Nykiel; Wojciech J. Miloch; Claudia Borries; Anna Morozova; Teresa Barata; William Engelke; et al. (Advances in Space Research, 2023)

Mitigation of higher order ionospheric effects on GNSS users in Europe - M. Mainul Hoque; N. Jakowski (GPS Solutions, 2008)

Higher order ionospheric effects in precise GNSS positioning - M. Mainul Hoque; N. Jakowski (Journal of Geodesy, 2007)